2020
DOI: 10.3168/jds.2019-16907
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Characterization of the milk protein expression profiles in dairy buffaloes with and without subclinical mastitis

Abstract: The aim of this study was to characterize the proteins present in milk whey from buffaloes with and without subclinical mastitis using a proteomic approach to identify differentially expressed proteins as potential biomarkers for this disease. Whey from Murrah buffaloes with subclinical mastitis was compared with whey from healthy animals using liquid chromatography-tandem mass spectrometry. The annotated protein databases for Bubalus bubalis and Bos taurus were used in the analysis, and the gene annotations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, the quarters assigned to the HSCC-L group at the beginning of the trial already displayed higher levels of four antimicrobial proteins compared to the quarters assigned to the HSCC-C group, namely chitinase-3-like protein 1 and CATHL3, CATHL6, CATHL7. Chitinase-3-like protein 1 participates in the innate immune response to microbial pathogens at the site of invasion [31]; its increase has been reported in the milk of cows and buffaloes with mastitis [32,33]. CATHLs are well-known antimicrobial proteins that play a major role in the immune defense of ruminants [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…However, the quarters assigned to the HSCC-L group at the beginning of the trial already displayed higher levels of four antimicrobial proteins compared to the quarters assigned to the HSCC-C group, namely chitinase-3-like protein 1 and CATHL3, CATHL6, CATHL7. Chitinase-3-like protein 1 participates in the innate immune response to microbial pathogens at the site of invasion [31]; its increase has been reported in the milk of cows and buffaloes with mastitis [32,33]. CATHLs are well-known antimicrobial proteins that play a major role in the immune defense of ruminants [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Whey fractions contain various proteins such as α-lactalbumin, β-lactoglobulin, lactoferrin, osteopontin (OPN), immunoglobulins, enzymes [including lactoperoxidase (LPO), superoxide dismutase (SOD), platelet-activating factor acetylhydrolase (PAFAH2), and alkaline phosphatase (ALPL)], and growth factors (including transforming growth factor β, insulin-like growth factor, epidermal growth factor, and heparin-binding EGF-like growth factor), which have a range of anti-inflammatory and immune cell regulatory effects . Three crucial milk fractions were significantly altered by mastitis, particularly the proteins linked to host defense and inflammation. Thus, compared with the abundant caseins, the lower proportion fractions may have a much stronger association with udder inflammation. However, the responses of these fractions to high SCC have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have examined the proteome with a focus on milk quality in food adulteration and nutritional value 19 21 . Two recent proteomic studies found changes in the milk proteome in water buffalo with subclinical mastitis 22 , 23 . Transcriptome analysis of milk revealed differences in the transcriptome of somatic cells of Murrah buffaloes and Sahiwal cattle 24 .…”
Section: Introductionmentioning
confidence: 99%